Ilmu Interdisipliner dan Multidisipliner dalam Manajemen Pendidikan Islam - Reinaldo, Antonio; Aprima, Septi Gia; Ardimen, Ardimen (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Problems related to Islamic education management can not only be solved with one solution. However, with the application of interdisciplinary and multidisciplinary science, problem solutions become more diverse and comprehensive. This study aims to explain how the application and implications of interdisciplinary and multidisciplinary science in Islamic education curriculum management. The research uses a qualitative approach with the library research method. The results of the analysis show that the importance of an interdisciplinary and multidisciplinary approach in the study of the Islamic education management curriculum, especially in facing current national and global issues